2007
DOI: 10.1084/jem.20070432
|View full text |Cite
|
Sign up to set email alerts
|

A novel inhibitor of the alternative pathway of complement reverses inflammation and bone destruction in experimental arthritis

Abstract: Complement is an important component of the innate and adaptive immune response, yet complement split products generated through activation of each of the three complement pathways (classical, alternative, and lectin) can cause inflammation and tissue destruction. Previous studies have shown that complement activation through the alternative, but not classical, pathway is required to initiate antibody-induced arthritis in mice, but it is unclear if the alternative pathway (AP) plays a role in established disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
97
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(100 citation statements)
references
References 28 publications
3
97
0
Order By: Relevance
“…In mouse models of arthritis clear evidence has been provided that the alternative pathway in particular, and not the classical pathway, is responsible for organ damage, based on experiments using complementdeficient animals (25,27) or a specific alternative pathway inhibitor (26). The present study provides evidence that human anti-CCP antibodies activate both the classical pathway and the alternative pathway and thereby mimic the results obtained from in vivo models.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In mouse models of arthritis clear evidence has been provided that the alternative pathway in particular, and not the classical pathway, is responsible for organ damage, based on experiments using complementdeficient animals (25,27) or a specific alternative pathway inhibitor (26). The present study provides evidence that human anti-CCP antibodies activate both the classical pathway and the alternative pathway and thereby mimic the results obtained from in vivo models.…”
Section: Discussionsupporting
confidence: 72%
“…C3 Ϫ/Ϫ , FB Ϫ/Ϫ , C5 Ϫ/Ϫ , and C5a receptor Ϫ/Ϫ mice are protected against induction of arthritis, whereas C1q Ϫ/Ϫ and MBL Ϫ/Ϫ mice are fully susceptible (25,26), indicating that in mouse models the alternative pathway is necessary and sufficient for disease induction (25,27,28). Now that ACPAs are increasingly recognized as major players in RA, it is of relevance to know if and how these antibodies activate complement.…”
mentioning
confidence: 99%
“…20 VSIG4 has been reported to regulate T-cell proliferation in vitro and in vivo, 21 and a soluble form of HsVSIG4 displays therapeutic potential in mouse models of arthritis by inhibiting autoreactive immune responses. 22 We have previously reported that VSIG4 signaling eliminates phagocytosed LMs by rapidly inducing CLIC3-dependent acidification of LM-containing phagosomes. 20 However, we also suspected that VSIG4 signaling might inhibit the intracellular growth of LMs that escaped into the macrophage cytosol, because some phagocytosed LMs manage to escape from phagosomes before VSIG4 was triggered and yet are eliminated.…”
Section: Introductionmentioning
confidence: 99%
“…The authors therefore suggested, that this area may be involved in C3b-dimerization or C3-C3b binding, and that compstatin may interfere with these interactions . A similar mechanism has been proposed for another complement inhibitor, the physiological receptor CRIg, that binds C3b at the same face of the β-chain (although via domains MG3/MG6) and selectively inhibits the alternative pathway convertases (Katschke et al 2007;Wiesmann et al 2006). …”
mentioning
confidence: 62%